The Effect of Pineapple (Ananas comosus L.) Juice Therapy on Reducing Uric Acid and Pain in the Elderly in Jatiroto Village - Umi Latifah; Zainal Abidin; Widya Addiarto (Al-Hijrah Indonesia, 2026)
Background: Gout arthritis is a prevalent degenerative joint disease among the elderly, characterized by hyperuricemia and joint pain due to monosodium urate crystal deposition. In Indonesia, its prevalence reaches 11.9%, highlighting the need for accessible, non-pharmacological interventions. Pineapple (Ananas comosus L.) contains bromelain and vitamin C, which exhibit anti-inflammatory and uricosuric properties. Objective: This study aimed to evaluate the effect of pineapple juice therapy on pain reduction and uric acid levels in elderly patients with gout arthritis. Methods: A quasi-experimental one-group pretest–posttest design was employed. Thirty elderly gout patients in Kotokan Hamlet, Jatiroto Village, were selected using a total sampling method. The intervention consisted of 200 mL of fresh pineapple juice consumed daily for seven days. Pain intensity was measured using the Numeric Rating Scale (NRS), and serum uric acid levels were assessed with a portable uric acid meter. Data were analyzed using the Wilcoxon signed-rank test (α = 0.05). Results: Post-intervention, pain levels decreased significantly, with 73% of respondents reporting mild pain and 27% reporting no pain. Uric acid levels also shifted significantly from 100% hyperuricemic at baseline to 33% within normal limits and 67% below normal post-intervention (p = 0.000). Conclusion: Pineapple juice therapy effectively reduces both pain intensity and uric acid levels in elderly individuals with gout arthritis. It is recommended as a safe, cost-effective, and complementary non-pharmacological therapy for community-based gout management.